Two new species and one newly recorded species of the genus Kamaka (Crustacea: Amphipoda) from the Hainan Province, South China Sea - Ren, Xian-Qiu; Sha, Zhong-Li (Zootaxa, 2013)
A total of 5 species of the genus Kamaka (Crustacea: Amphipoda) are identified from Hainan Province, South China Sea. In those, one species, Kamaka excavata Ariyama, 2007, is recorded for the first time in Chinese waters. Two new species, Kamaka corophina sp. n. and Kamaka foliacea sp. n., are described. A key to the Chinese species is provided. They were collected from littoral zone, mud flat in seaweed of mangrove side, brackish water and seawater, sifted out with sieve.